1999
DOI: 10.1523/jneurosci.19-18-08152.1999
|View full text |Cite
|
Sign up to set email alerts
|

Impaired K+Homeostasis and Altered Electrophysiological Properties of Post-Traumatic Hippocampal Glia

Abstract: Traumatic brain injury (TBI) can be associated with memory impairment, cognitive deficits, or seizures, all of which can reflect altered hippocampal function. Whereas previous studies have focused on the involvement of neuronal loss in post-traumatic hippocampus, there has been relatively little understanding of changes in ionic homeostasis, failure of which can result in neuronal hyperexcitability and abnormal synchronization. Because glia play a crucial role in the homeostasis of the brain microenvironment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
84
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(94 citation statements)
references
References 43 publications
9
84
1
Order By: Relevance
“…Because our previous molecular and physiological data in mouse and rat models of albumin-and TGF-b-induced seizures showed early activation of astrocytes (3,10), and specifically a robust excessive extracellular potassium accumulation upon repetitive stimulation at physiologically relevant frequencies (10-50 Hz) (10), we tested a potential role of such stimulation on neuronal excitability in the IL-6-treated cortices. Our recordings demonstrate a long-lasting depolarization (∼8 mV) upon afferent but not intracellular stimulation, predicting a 25% increase in the accumulation of extracellular potassium during neuronal activation, consistent with the notion of astrocytic dysfunction and reduced potassium buffering after insult (51,52) or during epileptogenesis (3,10). Overall, although additional experiments in different neuronal populations and experimental conditions (e.g., voltage clamp experiments under different holding membrane potentials) are required to rule out additional changes in synaptic properties, our experiments at an early time point during epileptogenesis suggest that IL-6 is sufficient to facilitate stimulus-dependent neuronal depolarization and hyperexcitability, likely due to failure in buffering of extracellular potassium.…”
Section: Discussionsupporting
confidence: 84%
“…Because our previous molecular and physiological data in mouse and rat models of albumin-and TGF-b-induced seizures showed early activation of astrocytes (3,10), and specifically a robust excessive extracellular potassium accumulation upon repetitive stimulation at physiologically relevant frequencies (10-50 Hz) (10), we tested a potential role of such stimulation on neuronal excitability in the IL-6-treated cortices. Our recordings demonstrate a long-lasting depolarization (∼8 mV) upon afferent but not intracellular stimulation, predicting a 25% increase in the accumulation of extracellular potassium during neuronal activation, consistent with the notion of astrocytic dysfunction and reduced potassium buffering after insult (51,52) or during epileptogenesis (3,10). Overall, although additional experiments in different neuronal populations and experimental conditions (e.g., voltage clamp experiments under different holding membrane potentials) are required to rule out additional changes in synaptic properties, our experiments at an early time point during epileptogenesis suggest that IL-6 is sufficient to facilitate stimulus-dependent neuronal depolarization and hyperexcitability, likely due to failure in buffering of extracellular potassium.…”
Section: Discussionsupporting
confidence: 84%
“…The same concept of BBB breakdown for therapeutic purposes (generally for the purpose of increasing drug delivery to the brain) has also revealed a previously unrecognized role for BBB breakdown (Oby & Janigro 2006) as a possible aetiologic mechanism in epileptogenesis. Several studies have shown that mechanisms such as the Na þ /K þ pump and glial cell uptake play an important role in the regulation of [K þ ] o (Janigro et al 1997;D'Ambrosio et al 1999;Ransom et al 2000;Walz 2000).…”
mentioning
confidence: 99%
“…Decrease of Kir4.1 channels in astrocytes has been described in multiple conditions, including intractable mesio-temporal lobe epilepsy (Bordey and Sontheimer, 1998), Huntington’s disease (Tong et al, 2014), hepatic encephalopathy (Obara-Michlewska et al, 2011) and traumatic brain injury (D’Ambrosio et al, 1999) where the severity of Kir4.1 loss increases with aging (Gupta and Prasad, 2013) In the case of mesio-temporal lobe epilepsy, seizure-associated reactive astrocytes expressed enhanced sodium conductance and decreased potassium conductance (Bordey and Sontheimer, 1998). Hyperglycemia has been shown to increase sodium conductance in dorsal root ganglion cells (Singh et al, 2013) so a similar alteration in sodium dynamics may increase spiking probability and could potentially contribute to the increased seizures observed in diabetic patients (Sabitha et al, 2001, Younes et al, 2014).…”
Section: 0 Discussionmentioning
confidence: 99%